The Negative Freedom and Politics of Modus Vivendi - Turčan, Ciprian (Journal of Education Culture and Society, 2023)
Aim. The aim of this study is to provide a selected theoretical-methodological analysis of the concept of negative freedom in relation to the political sphere of its application, to reveal and clarify the main political implications and normative claims that its recognition implies for political theory.Concept. From a methodological point of view, the study is based on three justified assumptions: (1) that in modern political philosophy the idea of individual freedom is the main normative basis for political theories, (2) that philosophical development has brought several competing concepts of this idea and (3) that from its own content the concept implies basic requirements for its social and political application. For the purposes of theoretical-methodological analysis, we distinguished two different moments in the concept of individual freedom (freedom as a question of will and freedom as a question of practice) and from their point of view we examined the selected concept of negative freedom in an attempt to reveal its implicit claims at the political level.Results. In the article, we have succeeded in formulating and arguing for the thesis that the concept of negative freedom in its applicability programmatically leads to a modus vivendi model of politics. We have shown that the concept of freedom and the model of politics are interrelated and normatively interdependent.Conclusion. The main conclusion of the study is that the above model of politics cannot be generalised and considered equally acceptable for all conceptions of freedom and the good life.